Selection Of Gas Condensate Wells To Increase Condensate Recovery In Gas Condensate Fields (Eurasian Research Bulletin, 2024)
This article describes the conditions for selecting wells and the sequence of processes performed when influencing wells to increase condensate recovery in gas condensate fields